The Factors that Affect Toward Performance and Cooperative Success - Darma, Dio (Archives of Business Research, 2020)
Performance of management in cooperatives is crucial in order to improve prosperity. Performance management is not only measured by the success of the business but also the ability to improve the welfare of members. Performance as a result of business activity does not stand alone but by several factors. Qualities of management, member participation, support employees, the environment are examples of factors that affect the performance and success of cooperatives. The failure of cooperatives often occur due to the quality of management is weak, the participation of members less, support employees who are weak and environmentally counter- productive. Therefore, there needs to be a synergy between the various factors that increase the performance of the cooperative board.